Investing in biodiversity : a review of Indonesiaʼs Integrated Conservation and Development Projects - Wells, Michael, 1954- (Washington, D.C. : World Bank, 1999)
Considers the ICDPs' (Integrated Conservation and Development Projects) overall contribution to conserving Indonesia's biodiversity; assesses their cost-effectiveness, sustainability, and replicability; and identifies lessons for future conservation efforts.
Includes bibliographical references.
oif 12/08/15
Loan
Keywords: Sustainable development -- Indonesia; Conservation of natural resources -- Indonesia; Biodiversity -- Indonesia